Large Mitochondrial DNA Deletions in HIV Sensory Neuropathy. (13th July 2021) - Roda, Ricardo H.; Bargiela, David; Chen, Weiran; Perry, Ken; Ellis, Ronald J.; Clifford, David B.; Bharti, Ajay; Kallianpur, Asha R.; Oliveira, Michelli F.; Diaz, Monica M.; Rubin, Leah H.; Gavegnano, Christina; et al.
Abstract : Objective: The primary objective of this study was to evaluate the correlation of large mitochondrial DNA (mtDNA) deletions in skin samples of people with HIV (PWH) with measures of neuropathy and prior exposure to therapy. We hypothesized that deletions would be associated with neuropathy. As secondary objectives, we determined the correlation of deletion burden with demographic data and neuropathy measures. Methods: In this retrospective cohort study, we measured the accumulation of large mtDNA deletions in skin biopsies from PWH recruited as part of the AIDS Clinical Trials Group (ACTG). Our cohort includes individuals with and without sensory neuropathy, as well as individuals with normal or abnormal skin biopsies. Skin biopsies, sural and peroneal nerve conduction studies, total neuropathy score, and deletion burden scores were measured, along with baseline demographic data such as age, CD4+ cell count, viral counts, and prior nucleoside reverse transcriptase inhibitor exposures. Results: Sixty-seven PWH were enrolled in the study. The mean age of the cohort (n = 67) was 44 years (SD 6.8, range 32–65 years), and 9 participants were female. The mean CD4+ T-cell count was 168 cells/mm 3 (SD 97 cells/mm 3, range 1–416 cells/mm 3 ) and mean viral load was 51, 129 copies/mL (SD 114, 586 copies/mL, range 147–657, 775 copies/mL). We determined that there was a correlation between the total mtDNA deletion and intraepidermal nerve fiber density (IENFD) ( r = −0.344, p = 0.04) and sural nerve amplitude ( r = −0.359, p = 0.004). Conclusions: Both IENFD and sural nerve amplitude statistically correlate with mitochondrial mutation burden in PWH, specifically in those with HIV-associated sensory neuropathy as assessed by skin biopsy.